Floristic changes induced by fire on Pinus sylvestris plantations in northwest of Spain - Nuñez, M. R.; Calvo, L.; Pando, V.; Bravo, F. (Forest Systems, 2008)
The effects of wildfire on vegetation regeneration in the understory of stands dominated by Pinus sylvestris L. in north-west Spain were analysed. In order to study changes in the composition of this community, three study areas dominated by Pinus sylvestris L. and burned by a summer wildfire were selected. In each area three permanent plots of 25 × 1 m2 was established. The cover percentage of plant species present, and the cover of life forms and richness were analysed yearly from the first to the fourth year after fire. Total cover values generally increased throughout the study period. The species that appeared during the first years were those that would dominate in the mature stage, such as Erica australis L. and Pterospartum tridentatum (L.) Willk, both species being typical resprouters. Other species that appeared from the first year are typical seeders like Pinus sylvestris L. and Halimium alyssoides (Lam.) K. Koch. Floristic richness values showed higher values during the first year after fire than in the original situation, due to the fast recovery of the herbaceous species in the open spaces created by fire. After the first year changes in richness values were not significant